Investigating the demographic “profile” of the European Socio-economic Classification (ESeC) for Greece, 2002-2010 - Yfanti, Aggeliki (The Greek Review of Social Research, 2022)
In social sample survey research and the census, international classifications have been developed for the measurement of background variables ensuring overtime and cross-national comparability. In this respect, Eurostat developed the European socio-economic classification (ESeC) for the study of the social structure evolution and social change. However, the theoretical conception of this schema has been criticized especially for its implementation in Southern Europe. In this paper, we assess the implementation of ESeC by investigating its demographic “profile” in Greece. The analysis is based on the 2002, 2004, 2008 and 2010 European Social Survey datasets for Greece.